Enhancing students’ digital skills with GENESI5: Generative AI for creative writing in the Society 5.0 era - Hanafi, Yusuf; Nabila, Alifian; Hayati, Early Ni’mah; Alfarizzi, Muhammad; Sukur, Abdul; Kusuma, Arum Dyan; Amalia, D. Adnindya; Hasan, Zaiful; M. Akhirudin Nurul Huda (PERDIKAN (Journal of Community Engagement), 2024)
The advancement of technology in the Society 5.0 era necessitates higher digital literacy, particularly for students of the next generation. The application of AI technology has emerged as a significant solution to enhance digital skills, which is relevant not only in education but also in supporting sustainable programs such as Adiwiyata. However, the implementation of this technology among students is still relatively low, requiring interventions like specialized training. This study aims to improve the digital skills of students at SMP Negeri 8 Malang through the “GENESI5” training program, which integrates generative AI technology into both learning and extracurricular activities. A total of 52 students participated in the two-day training. The method employed in this study is Participatory Action Research (PAR), which actively involves students in the learning process. The study's findings indicate a significant improvement in students' digital skills, as demonstrated by their ability to use generative AI to create creative works aligned with the Adiwiyata theme. Therefore, this training successfully enhanced students' technological literacy and motivated them to create innovatively in the Society 5.0 era.[Kemajuan teknologi di era Society 5.0 menuntut kemampuan literasi digital yang lebih tinggi, terutama bagi siswa sebagai generasi penerus. Pemanfaatan teknologi AI telah menjadi salah satu solusi untuk meningkatkan keterampilan digital, yang tidak hanya relevan dalam dunia pendidikan, tetapi juga untuk mendukung program berkelanjutan seperti Adiwiyata. Namun, penerapan teknologi ini di kalangan siswa masih tergolong rendah, sehingga diperlukan intervensi berupa pelatihan khusus. Penelitian ini bertujuan untuk meningkatkan keterampilan digital siswa SMP Negeri 8 Malang melalui pelatihan “GENESI5”, yang mengintegrasikan teknologi generative AI dalam proses pembelajaran dan ekstrakurikuler. Sebanyak 52 siswa mengikuti pelatihan selama dua hari. Metode yang digunakan dalam penelitian ini adalah Participatory Action Research (PAR), yang melibatkan siswa secara aktif dalam proses pembelajaran. Hasil penelitian menunjukkan peningkatan signifikan dalam keterampilan digital siswa, terlihat dari kemampuan mereka memanfaatkan generative AI untuk menghasilkan karya kreatif sesuai dengan tema adiwiyata. Dengan demikian, pelatihan ini berhasil meningkatkan literasi teknologi siswa serta memotivasi mereka untuk berkarya secara inovatif di era Society 5.0.]